Surface-treated glass cloth, prepreg and printed circuit board
A surface-treated glass cloth with a silane coupling agent and styrene monomer-derived structural unit addresses adhesion issues with the matrix resin, ensuring effective impregnation and reducing defects, thereby improving insulation reliability and processability in printed wiring boards.
Patent Information
- Application Number
- JP2023115601
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
AI Technical Summary
The adhesion between glass cloth with a low dielectric constant and low dielectric loss tangent and the matrix resin is poor, leading to insulation reliability issues and defects such as striation voids, which cause ion migration and short circuits in printed wiring boards.
A surface-treated glass cloth with a surface treatment layer containing a silane coupling agent and a structural unit derived from a styrene monomer, where the integral value of the peak of protons belonging to a benzene ring measured by H-NMR is between 28 to 46% of the total, ensuring excellent adhesion and impregnation of the matrix resin without making the texture excessively hard.
The solution provides a prepreg with improved insulation reliability and processability by maintaining matrix resin impregnation, reducing defects like striation voids, and enhancing the adhesion between the glass cloth and matrix resin.
Smart Images

Figure 2025012628000001 
Figure 2025012628000002 
Figure 2025012628000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface-treated glass cloth, a prepreg, and a printed wiring board. [Background technology]
[0002] In recent years, with the development of communication technology, the frequencies used in communication have been increasing into the GHz range. However, the higher the frequency, the greater the effects of the dielectric constant and dielectric tangent of the materials used in printed wiring boards, resulting in greater signal attenuation due to dielectric loss.
[0003] In the field of communication technology, therefore, in order to reduce the dielectric loss of high frequency signals, a prepreg is used in which a glass cloth having a low dielectric constant and a low dielectric dissipation factor is impregnated with a matrix resin having a low dielectric constant and a low dielectric dissipation factor. However, the adhesion between the glass cloth having a low dielectric constant and a low dielectric dissipation factor and the matrix resin having a low dielectric constant and a low dielectric dissipation factor is poor in the prepreg, resulting in a problem of reduced insulation reliability, etc.
[0004] Usually, glass cloth is surface-treated by providing a surface treatment layer containing a silane coupling agent on the surface thereof in order to improve affinity with the matrix resin and obtain excellent adhesion. For example, a surface-treated glass cloth is known that has a surface treatment layer on the surface of the glass cloth, the surface treatment layer containing a silane coupling agent and a surface treatment resin having a functional group capable of forming a chemical bond with the matrix resin (see, for example, Patent Document 1).
[0005] According to the surface-treated glass cloth described in Patent Document 1, by providing a surface treatment layer on the surface of the glass cloth, the surface treatment layer containing the silane coupling agent and the surface treatment resin having a functional group capable of forming a chemical bond with the matrix resin, it is possible to obtain a printed wiring board in which the occurrence of cracks during machining and the decrease in solder heat resistance are suppressed. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 3897699 Summary of the Invention [Problem to be solved by the invention]
[0007] However, while increasing the amount of the surface treatment layer applied to the glass cloth improves the adhesion to the matrix resin, it also makes it difficult for the matrix resin to penetrate between the glass filaments of the glass fibers constituting the glass cloth, which can cause defects such as striation voids, and the texture of the obtained surface-treated glass cloth becomes excessively hard, causing wrinkles during the production of a prepreg, resulting in poor processability.
[0008] The striation voids refer to a state in which, when the impregnation of the glass fibers constituting the glass cloth with the matrix resin is low, the matrix resin hardens before flowing between the glass filaments of the glass fibers, and the matrix resin does not impregnate the glass filaments, forming a cavity between the glass filaments. For example, if the striation voids exist in a prepreg, when a printed wiring board is manufactured using the prepreg, the metal constituting the wiring or via undergoes ion migration at the interface between the glass fibers and the matrix resin, causing a short circuit due to CAF (Conductive Anodic Filament) or the like, thereby reducing the insulation reliability of the printed wiring board.
[0009] Therefore, an object of the present invention is to provide a surface-treated glass cloth which overcomes the above-mentioned disadvantages, has excellent adhesion to a matrix resin, does not impregnate the glass fibers with a matrix resin even when the amount of adhesion of the surface treatment layer is increased, and does not become excessively hard in texture. [Means for solving the problem]
[0010] In order to achieve the above object, the present invention provides a surface-treated glass cloth having a surface treatment layer on a surface thereof, the surface treatment layer containing a silane coupling agent and a structural unit derived from a styrene-based monomer, 1 and a surface treatment resin in which the integral value of the peak of a proton belonging to a benzene ring as measured by H-NMR is in the range of 28 to 46% of the integral value of the peaks of all protons.
[0011] The surface-treated glass cloth of the present invention has an excellent adhesiveness with the matrix resin because the surface-treated layer contains the silane coupling agent and the surface-treatment resin, and even if the amount of adhesion of the surface-treated layer is increased, the impregnation of the matrix resin into the glass fiber is not impaired, and the texture does not become excessively hard. As a result, the surface-treated glass cloth of the present invention can obtain a prepreg with excellent insulation reliability without generating defects such as striation voids, and can obtain excellent processability when producing the prepreg.
[0012] The term "increasing the amount of adhesion of the surface treatment layer" means that the amount of adhesion of the surface treatment layer is 0.8 mass % or more based on the total amount of the surface-treated glass cloth.
[0013] The surface treatment resin contained in the surface treatment layer is 1 When the integral value of the peak of the protons belonging to the benzene ring measured by H-NMR is less than 28% of the integral value of the peaks of all protons, the texture of the surface-treated glass cloth becomes hard, and the impregnation of the matrix resin into the glass fibers of the surface-treated glass cloth of the present invention decreases. 1 When the integral value of the peak of a proton assigned to a benzene ring measured by 1 H-NMR exceeds 46% of the integral value of the peaks of all protons, the impregnation of the glass fibers of the surface-treated glass cloth with the matrix resin decreases.
[0014] In the surface-treated glass cloth of the present invention, the silane coupling agent contained in the surface treatment layer is not particularly limited, but is preferably methacrylsilane from the viewpoint of adhesion to the radical-polymerizable thermosetting resin used as the matrix resin. Examples of the radical-polymerizable thermosetting resin used as the matrix resin include polyphenylene ether, LCP, cycloolefin polymer, divinylbenzene resin, maleimide resin, etc.
[0015] In the surface-treated glass cloth of the present invention, the styrene-based monomer is preferably one or more monomers selected from styrene-based monomers represented by the following general formula (1).
[0016] [ka] [In the formula, R1 is hydrogen or an alkyl group having 1 to 2 carbon atoms, and R2 to R6 are each independently hydrogen, a halogen atom, an alkyl group, an alkenyl group, an alkynyl group, or an aryl group, and may contain a heteroatom.]
[0017] Specific examples of the styrene monomer include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, 4-tert-butylstyrene, o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-ethoxystyrene, m-ethoxystyrene, p-ethoxystyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, o-bromostyrene, m-bromostyrene, p-bromostyrene, o-fluorostyrene, m-fluorostyrene, p-fluorostyrene, o-chloromethylstyrene, m-chloromethylstyrene, and p-chloromethylstyrene. Of these, styrene is preferred.
[0018] In the surface-treated glass cloth of the present invention, the surface treatment layer may be a single layer consisting of a mixture of the silane coupling agent and the surface treatment resin. However, from the viewpoint that the silane coupling agent has excellent reactivity with glass and the surface treatment resin has excellent reactivity with a matrix resin, it is preferable that the surface treatment layer consists of a first surface treatment layer containing the silane coupling agent and a second surface treatment layer containing the surface treatment resin.
[0019] In the surface-treated glass cloth of the present invention, the adhesion amount of the surface treatment layer is preferably in the range of 0.8 to 5.0 mass % based on the total amount of the surface-treated glass cloth. If the adhesion amount of the surface treatment layer is less than 0.8 mass % based on the total amount of the surface-treated glass cloth, the adhesion to the matrix resin may be insufficient, whereas if it exceeds 5.0 mass %, the surface-treated glass cloth may not be stably produced.
[0020] The surface-treated glass cloth of the present invention preferably has a dielectric loss tangent in the range of 0.0001 to 0.0040 at a measurement frequency of 10 GHz. It is technically difficult to make the dielectric loss tangent of the surface-treated glass cloth of the present invention less than 0.0001, and if the dielectric loss tangent exceeds 0.0040, the dielectric loss of high-frequency signals may not be sufficiently reduced when the surface-treated glass cloth is made into a prepreg or a printed wiring board.
[0021] The prepreg and printed wiring board of the present invention are characterized by including the surface-treated glass cloth of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Next, the embodiment of the present invention will be described in more detail.
[0023] The surface-treated glass cloth of the present embodiment is, for example, a surface-treated glass cloth having a low dielectric constant and a low dielectric tangent and provided with a surface-treated layer on the surface thereof, the surface-treated layer containing a silane coupling agent and a structural unit derived from a styrene-based monomer, 1and a resin for surface treatment in which the integral value of the peak of a proton belonging to a benzene ring as measured by H-NMR is in the range of 28 to 46% of the integral value of the peaks of all protons.
[0024] The glass cloth having a low dielectric constant and a low dielectric loss tangent is a glass fiber fabric woven using glass fiber yarns having a glass composition with a low dielectric constant and a low dielectric loss tangent as warp and weft yarns. Examples of the glass composition having a low dielectric constant and a low dielectric tangent include silica glass, D glass, NE glass, and L glass. For example, a composition containing SiO2 in the range of 48.0 to 62.0 mass%, B2O3 in the range of 17.0 to 26.0 mass%, Al2O3 in the range of 9.0 to 18.0 mass%, CaO in the range of 0.1 to 9.0 mass%, MgO in the range of 0 to 6.0 mass%, Na2O, K2O, and Li2O in a total range of 0.05 to 0.5 mass%, TiO2 in the range of 0 to 5.0 mass%, SrO in the range of 0 to 6.0 mass%, F2 and Cl2 in a total range of 0 to 3.0 mass%, and P2O5 in the range of 0 to 6.0 mass% can be mentioned.
[0025] The silane coupling agent constituting the surface treatment layer is not particularly limited, and can be, for example, aminosilane, chlorosilane, epoxysilane, mercaptosilane, vinylsilane, (meth)acrylsilane, cationic silane, etc., but is preferably methacrylsilane or cationic silane, and more preferably methacrylsilane. The methacrylsilane can be, for example, 3-methacryloxypropyltrimethoxysilane, and the cationic silane can be, for example, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, N-phenyl-3-aminopropyltrimethoxysilane hydrochloride, etc.
[0026] The surface treatment resin constituting the surface treatment layer contains a structural unit derived from a styrene-based monomer, and examples of the styrene-based monomer include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, 4-tert-butylstyrene, o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-ethoxystyrene, m-ethoxystyrene, p-ethoxystyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, o-bromostyrene, m-bromostyrene, p-bromostyrene, o-fluorostyrene, m-fluorostyrene, p-fluorostyrene, o-chloromethylstyrene, m-chloromethylstyrene, and p-chloromethylstyrene.
[0027] The surface treatment resin constituting the surface treatment layer may contain a structural unit derived from a styrene-based monomer and a structural unit derived from another polymerizable monomer. The other polymerizable monomer is not particularly limited, but is preferably a (meth)acrylic acid ester-based monomer.
[0028] As the (meth)acrylic acid ester monomer, for example, one or more of (meth)acrylic acid alkyl esters, (meth)acrylic acid hydroxyalkyl esters, (meth)acrylic acid alkoxyalkyl esters, (meth)acrylic acid aralkyl esters, and (meth)acrylic acid aryl esters can be used, but it is preferable to use (meth)acrylic acid alkyl esters.
[0029] Examples of the (meth)acrylic acid alkyl ester include (meth)acrylic acid alkyl esters having a linear or branched alkyl group, and alicyclic (meth)acrylic acid alkyl esters.
[0030] Examples of the (meth)acrylic acid alkyl ester having a linear or branched alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, and n-octyl (meth)acrylate. acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate.
[0031] Examples of the alicyclic (meth)acrylic acid alkyl ester include cyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and dicyclopentenyl (meth)acrylate.
[0032] The other resin component may be one or more of the (meth)acrylic acid alkyl esters, preferably a (meth)acrylic acid alkyl ester having a linear or branched alkyl group having a carbon atom number of 1 to 18, more preferably 1 to 12. Examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate and 2-ethylhexyl (meth)acrylate.
[0033] The surface treatment resin is preferably an emulsion resin of a polymer of the styrene monomer and another polymerizable monomer. Examples of the emulsion resin include an emulsion of one or more of the emulsion resins of the polymer of the styrene monomer and another polymerizable monomer, and an emulsion of a mixture of a styrene resin and an acrylic resin.
[0034] The emulsion resin can be obtained by polymerizing one or more polymerizable monomer components that form resin particles in an aqueous medium such as water that is usually contained in the emulsion resin. Alternatively, the emulsion resin can be obtained by post-emulsifying resin particles produced separately from the aqueous medium by a method such as forced emulsification or self-emulsification. However, it is preferable that the emulsion resin is obtained by emulsion polymerization of polymerizable monomer components that form resin particles in an aqueous medium.
[0035] The aqueous medium is preferably water, and water alone may be used, or a mixture of water and an organic solvent may be used. The organic solvent may be, for example, methanol, ethanol, isopropanol, ethyl carbitol, and N-methylpyrrolidone, but is not limited thereto, and one or more of the organic solvents may be used. The resin constituting the emulsion resin preferably has a glass transition temperature in the range of 20 to 60°C, more preferably in the range of 25 to 55°C, so that the resin can be uniformly applied to the surface of the glass fiber in the step of forming a surface treatment layer on the glass cloth described later, and the emulsion resin can be uniformly spread.
[0036] The surface treatment resin is 1Since the integral value of the peak of the protons belonging to the benzene ring measured by H-NMR is in the range of 28 to 46% of the integral value of the peaks of all protons, when a surface treatment layer is formed on the surface of the surface-treated glass cloth of this embodiment together with the silane coupling agent, excellent adhesion can be obtained between the glass fibers and the matrix resin, and even if the adhesion amount of the surface treatment layer is increased, the impregnation of the matrix resin into the glass fibers of the surface-treated glass cloth is not impaired. Furthermore, the texture of the surface-treated glass cloth does not become too hard, so that excellent processability can be obtained when producing a prepreg.
[0037] The surface treatment resin is 1 When the integral value of the peak of the protons belonging to the benzene ring measured by H-NMR is less than 28% of the integral value of the peak of all protons, when a surface treatment layer is formed on the surface of the surface-treated glass cloth of this embodiment together with the silane coupling agent, the texture of the surface-treated glass cloth becomes hard, and the impregnation of the glass fibers of the surface-treated glass cloth with the matrix resin decreases. 1 When the integral value of the peak of a proton assigned to a benzene ring measured by H-NMR exceeds 46% of the integral value of the peaks of all protons, when a surface treatment layer is formed on the surface of the surface-treated glass cloth of this embodiment together with the silane coupling agent, the impregnation of the glass fibers of the surface-treated glass cloth with the matrix resin decreases.
[0038] The above 1 The measurement by H-NMR can be carried out, for example, using a nuclear magnetic resonance analyzer manufactured by Oxford Instruments (trade name: Pulsar HFC) and using a solution prepared by dissolving the above-mentioned surface treatment resin in chloroform-D1 (CDCl3) containing tetramethylsilane (TMS) as an internal standard as a solvent at a concentration in the range of 0.1 to 10 mass % as a sample. 1From the results of H-NMR measurement, the peaks with a chemical shift δ in the range of 6.3 to 7.2 ppm based on the peak of the internal standard are taken as peaks of protons belonging to the benzene ring, and the ratio of the integral value of the peak of protons belonging to the benzene ring to the integral value of all proton peaks excluding the peak of the internal standard and the peak of chloroform (CHCl3) contained in small amounts in chloroform-D1 is calculated.
[0039] In the surface-treated glass cloth of this embodiment, a single layer consisting of a mixture of the silane coupling agent and the surface treatment resin may be used. However, from the viewpoint that the silane coupling agent has excellent reactivity with glass and the surface treatment resin has excellent reactivity with a matrix resin, it is preferable that the surface treatment layer consists of a first surface treatment layer containing the silane coupling agent and a second surface treatment layer containing the surface treatment resin.
[0040] The adhesion amount of the surface treatment layer in the glass cloth is preferably in the range of 0.8 to 5.0 mass% based on the total amount of the surface-treated glass cloth. If the adhesion amount of the surface treatment layer is less than 0.8 mass% based on the total amount of the surface-treated glass cloth, the adhesion to the matrix resin may be insufficient, and if it exceeds 5.0 mass%, the surface-treated glass cloth may not be stably produced. From the viewpoint of adhesion to the matrix resin and production stability, the adhesion amount is more preferably in the range of 1.0% to 3.0%, and even more preferably in the range of 1.2% to 2.0%.
[0041] In addition, the surface-treated glass cloth of this embodiment preferably has a dielectric loss tangent in the range of 0.0001 to 0.0040 at a measurement frequency of 10 GHz. It is technically difficult to make the dielectric loss tangent of the surface-treated glass cloth of this embodiment less than 0.0001, and if the dielectric loss tangent exceeds 0.0040, the dielectric loss of high-frequency signals may not be sufficiently reduced when the surface-treated glass cloth is made into a prepreg or a printed wiring board. From the viewpoint of productivity and processability of the glass fiber, the dielectric loss tangent is more preferably in the range of 0.0008 to 0.0030.
[0042] Next, the surface-treated glass cloth of this embodiment can be produced, for example, as follows.
[0043] First, glass raw materials prepared to obtain a glass composition for glass fiber having a predetermined glass composition are melted in a glass melting furnace to obtain molten glass (a melt of the glass composition for glass fiber). The glass composition may be, for example, the glass composition having a low dielectric constant and a low dielectric loss tangent.
[0044] The content of each component of the glass composition can be measured by using an ICP emission spectrometer for Li, which is a light element, and by using a wavelength dispersive X-ray fluorescence analyzer for other elements. Specifically, the content of each component of the glass composition can be measured as follows.
[0045] First, the glass fibers are cut to an appropriate size, then placed in a platinum crucible and melted in an electric furnace at 1550°C for 6 hours while stirring to obtain a homogeneous molten glass. If organic matter is attached to the glass fiber surface or if the glass fibers are contained in an organic material (resin) mainly as a reinforcing material, the organic matter is removed by, for example, heating in a muffle furnace at 300 to 650°C for about 2 to 24 hours before use.
[0046] Next, the obtained molten glass is poured onto a carbon plate to produce glass cullet, which is then crushed and powdered to produce glass powder. The light element Li is quantitatively analyzed using an ICP emission spectrometer after the glass powder is thermally decomposed with acid. The other elements are quantitatively analyzed using a wavelength dispersive X-ray fluorescence analyzer after the glass powder is molded into a disk shape using a press. The results of these quantitative analyses are converted into oxides to calculate the content and total amount of each component, and the content (mass%) of each of the above-mentioned components can be calculated from these values.
[0047] The molten glass is then discharged from a vessel (bushing) having a nozzle plate on which several to several thousand nozzle tips are formed, and is cooled and solidified while being stretched by winding at high speed to form a fiber (this operation is sometimes called "spinning"), thereby forming a glass filament. The bushing is made of a precious metal such as platinum.
[0048] Here, the glass filament discharged from one nozzle tip or hole and cooled and solidified usually has a perfectly circular cross-sectional shape and a diameter of 3.0 to 10 μm. On the other hand, when the nozzle tip has a non-circular shape and has a protrusion or a notch for quenching the molten glass, it is possible to obtain a glass filament having a non-circular (e.g., elliptical or oval) cross-sectional shape by controlling the temperature conditions.
[0049] Next, 20 to 300 of the glass filaments formed as described above are bundled by applying a bundling agent (sometimes called a primary sizing agent) with an applicator, and then wound around a collet to form a glass strand (glass fiber bundle).
[0050] Next, the formed glass strands are used as warp glass strands and weft glass strands, and the warp glass strands are used as warp threads and the weft glass strands are used as weft threads to weave a glass cloth. The weaving can be carried out by a loom known per se, and examples of the loom include a jet loom such as an air jet or water jet loom, a shuttle loom, and a rapier loom. Examples of the weaving method used by the loom include a plain weave, a satin weave, a tanned weave, and a twill weave, and from the viewpoint of production efficiency, a plain weave is preferred.
[0051] Next, the glass cloth is subjected to a deoiling treatment, a surface treatment, or a fiber-opening treatment to obtain the surface-treated glass cloth of the present embodiment. The order of the deoiling treatment, surface treatment, or fiber-opening treatment is not particularly limited, but may be, for example, the fiber-opening treatment, the deoiling treatment, and the surface treatment in that order.
[0052] Examples of the opening treatment include a treatment for expanding the yarn width of the warp yarns and the weft yarns by applying a tension in the range of 30 to 200 N to the warp yarns of the glass cloth and carrying out opening by water flow pressure, opening by high-frequency vibration using a liquid as a medium, opening by the pressure of a fluid having a surface pressure, opening by pressure using a roll, or the like.
[0053] In the deoiling treatment, the glass cloth after the opening treatment is placed in a heating furnace at an atmospheric temperature in the range of 350 to 400°C for a period in the range of 32 to 75 hours, whereby the sizing agent adhering to the glass cloth is thermally decomposed.
[0054] The surface treatment is carried out by first immersing the glass cloth after the deoiling treatment in a silane coupling agent treatment liquid containing a silane coupling agent at a concentration in the range of 0.3 to 4.0 mass %, squeezing out excess water, and then drying by heating at a temperature in the range of 80 to 180°C for a time in the range of 1 to 30 minutes to form a first surface treatment layer, and then forming a second surface treatment layer containing a structural unit derived from a styrene-based monomer, 1 The glass cloth on which the first surface treatment layer has been formed is immersed in a surface treatment resin composition treatment liquid containing a surface treatment resin at a concentration in the range of 3 to 20 mass % in which the integral value of the proton peaks belonging to the benzene rings measured by H-NMR is in the range of 28 to 46% of the integral value of the peaks of all protons, and after squeezing out excess water, the glass cloth is heated and dried at a temperature in the range of 80 to 180°C for a time in the range of 1 to 30 minutes to form a second surface treatment layer on the first surface treatment layer.
[0055] The silane coupling agent treatment liquid contains, for example, the silane coupling agent, an organic acid, and a surfactant.
[0056] As the silane coupling agent, for example, methacrylsilanes such as 3-methacryloxypropyltrimethoxysilane, or cationic silanes such as N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, N-phenyl-3-aminopropyltrimethoxysilane hydrochloride, etc. can be used.
[0057] Examples of the organic acid include acetic acid, formic acid, propionic acid, malonic acid, maleic acid, succinic acid, oxalic acid, malic acid, and citric acid. Acetic acid is preferred because of its ease of handling.
[0058] Examples of the surfactant include a nonionic surfactant, a cationic surfactant, an anionic surfactant, and an amphoteric surfactant. In this embodiment, the surfactant may be used alone or in combination of two or more kinds.
[0059] Examples of nonionic surfactants include ethylene oxide propylene oxide alkyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene-polyoxypropylene block copolymers, alkyl polyoxyethylene-polyoxypropylene block copolymer ethers, polyoxyethylene fatty acid esters, polyoxyethylene fatty acid monoesters, polyoxyethylene fatty acid diesters, polyoxyethylene sorbitan fatty acid esters, glycerol fatty acid ester ethylene oxide adducts, polyoxyethylene castor oil ethers, hydrogenated castor oil ethylene oxide adducts, alkylamine ethylene oxide adducts, fatty acid amide ethylene oxide adducts, glycerol fatty acid esters, polyglycerin fatty acid esters, pentaerythritol fatty acid esters, sorbitol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyhydric alcohol alkyl ethers, fatty acid alkanolamides, acetylene glycol, acetylene alcohol, ethylene oxide adducts of acetylene glycol, and ethylene oxide adducts of acetylene alcohol.
[0060] Examples of cationic surfactants include alkyl dimethyl benzyl ammonium chloride, alkyl trimethyl ammonium chloride, alkyl dimethyl ethyl ammonium ethyl sulfate, higher alkyl amine salts, ethylene oxide adducts to higher alkyl amines, condensates of higher fatty acids and polyalkylene polyamines, salts of esters of higher fatty acids and alkanolamines, salts of higher fatty acid amides, imidazoline cationic surfactants, and alkyl pyridinium salts. Examples of higher alkyl amine salts include acetates and hydrochlorides.
[0061] Examples of anionic surfactants include higher alcohol sulfates, higher alkyl ether sulfates, α-olefin sulfates, alkylbenzene sulfonates, α-olefin sulfonates, reaction products of fatty acid halides and N-methyltaurine, dialkyl sulfosuccinates, higher alcohol phosphates, and phosphates of higher alcohol ethylene oxide adducts.
[0062] Examples of amphoteric surfactants include amino acid amphoteric surfactants, betaine amphoteric surfactants, and imidazoline amphoteric surfactants. Examples of amino acid amphoteric surfactants include alkali metal salts of alkylaminopropionic acid. Examples of betaine amphoteric surfactants include alkyldimethylbetaines.
[0063] The surface treatment resin composition treatment liquid is a liquid obtained by diluting an emulsion resin containing a structural unit derived from the styrene-based monomer in the range of 3 to 20% by mass. Examples of the emulsion resin include styrene-containing acrylic resin, styrene-butadiene resin, and acrylonitrile-butadiene-styrene copolymer resin (ABS resin).
[0064] As a result, it is possible to obtain the surface-treated glass cloth of this embodiment having a dielectric loss tangent in the range of 0.0001 to 0.0040 at a measurement frequency of 10 GHz.
[0065] The prepreg of this embodiment includes the surface-treated glass cloth of this embodiment and a matrix resin impregnated into the surface-treated glass cloth. The matrix resin may be any resin that is used as a matrix resin for a prepreg, and is not particularly limited. However, the surface-treated glass cloth of this embodiment can be particularly advantageously used when the matrix resin is a resin with a low dielectric constant and a low dielectric loss tangent. Examples of the resin with a low dielectric constant and a low dielectric loss tangent include polyphenylene ether, LCP, cycloolefin polymer, divinylbenzene resin, and maleimide resin.
[0066] The prepreg of this embodiment can be produced by immersing the surface-treated glass cloth of this embodiment in a varnish containing the matrix resin and pre-drying it at a temperature in the range of 110 to 160°C for a time in the range of 5 to 20 minutes.
[0067] The printed wiring board of this embodiment can be obtained, for example, by curing the prepreg of this embodiment described above.
[0068] Next, examples of the present invention and comparative examples will be described. EXAMPLES
[0069] Example 1 In this embodiment, a low dielectric constant and low dielectric tangent glass fiber with a filament diameter of 7 μm and a yarn weight of 20.8 g / 1000 m was used to fabricate a spunbond ... 2) was woven into a glass cloth. The dielectric constant of the glass fiber at a measurement frequency of 10 GHz was 4.7, and the dielectric loss tangent was 0.0025. The glass composition of the glass fiber contained 54.5 mass% of SiO2, 19.4 mass% of B2O3, 14.6 mass% of Al2O3, 4.2 mass% of MgO, 4.1 mass% of CaO, 1.9 mass% of TiO2, 0.1 mass% of Fe2O3, a total of 0.2 mass% of Li2O, Na2O and K2O, and 1.0 mass% of F2, based on the total amount of the glass fiber. In Tables 1 and 2, the glass composition is referred to as "low dielectric glass."
[0070] Next, the woven glass cloth was subjected to a fiber-opening treatment using a high-pressure water flow at a temperature of 40°C and a pressure of 2 MPa, and then heated at a temperature of 410°C for 36 hours to perform a deoiling treatment, thereby preparing a glass cloth to be surface-treated.
[0071] Next, the deoiled glass cloth was immersed in a silane coupling agent treatment liquid, and after squeezing out excess water, it was heated and dried at a temperature of 110°C for 5 minutes to form a first surface treatment layer on the surface of the glass cloth. Next, the glass cloth on which the first surface treatment layer was formed was immersed in a styrene-based emulsion resin treatment liquid, and after squeezing out excess water, it was heated and dried at a temperature of 110°C for 5 minutes to form a second surface treatment layer, and a surface-treated glass cloth was obtained. The surface-treated glass cloth has a surface treatment layer consisting of a first surface treatment layer and a second surface treatment layer on the surface of the glass cloth, and the second surface treatment layer is formed on the first surface treatment layer.
[0072] The silane coupling agent treatment solution was prepared by mixing 3-methacryloxypropyltrimethoxysilane (manufactured by Dow Corning Toray Co., Ltd.) as the silane coupling agent with water to give a composition of 1.0 mass% solids, 0.1 mass% acetic acid, and 0.05 mass% surfactant (polyoxyethylene alkyl ether), and stirring with a magnetic stirrer for 1 hour to prepare 2 liters.
[0073] The styrene-based emulsion resin treatment liquid was prepared by diluting an emulsion obtained by polymerizing a styrene-based monomer (styrene) and a (meth)acrylic acid ester-based monomer (2-ethylhexyl acrylate and methyl methacrylate) in a mass ratio of 75:25 with water to 10 mass % to prepare 2 liters. The styrene-based emulsion resin was synthesized by a known emulsion polymerization (for example, Japanese Patent No. 7217481, paragraph 0091 (Production Example 1)), but may be synthesized by a known solution polymerization, bulk polymerization, suspension polymerization, etc. The ratio of 2-ethylhexyl acrylate and methyl methacrylate in the styrene-based emulsion resin was adjusted so as to obtain a predetermined Tg.
[0074] The styrene-based emulsion resin is a copolymer resin of a styrene-based monomer and a (meth)acrylic acid ester-based monomer, and the copolymer resin has a styrene content of 75% by mass and a glass transition temperature (Tg) of 35°C.
[0075] Next, the surface-treated glass cloth was cut into pieces measuring 350 mm×400 mm to obtain surface-treated glass cloth pieces, which were then immersed in polyphenylene ether resin varnish and pre-dried at a temperature of 150° C. for 10 minutes to obtain prepregs.
[0076] The polyphenylene ether resin varnish contains 450 parts by mass of toluene (manufactured by Mitsubishi Gas Chemical Co., Ltd., product name: OPE-2St), 100 parts by mass of triallyl isocyanurate (manufactured by Evonik Japan Co., Ltd., product name: TAICROS), 4 parts by mass of 1,3-di(t-butylperoxyisopropyl)benzene (manufactured by NOF Corporation, product name: Perbutyl P), and 250 parts by mass of toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). The triallyl isocyanurate acts as a crosslinking agent.
[0077] Next, four sheets of the prepreg were laminated, cellophane films were placed on top and bottom, and the laminate was heated at 205°C and 18 kgf / cm using a vacuum hot press (manufactured by Kitagawa Seiki Co., Ltd.). 2The laminate was heated and pressed at a pressure of 1000 MPa for 1 hour in a vacuum to obtain a laminate with a thickness of approximately 0.3 mm as a simulated printed wiring board.
[0078] Next, the amount of the surface treatment layer attached, the glass transition temperature (Tg) of the emulsion resin, and the like of the surface-treated glass cloth obtained in this example were measured. 1 The ratio of the integral value of the peak of the protons assigned to the benzene ring to the integral value of the peak of all protons measured by H-NMR ( 1 The H-NMR peak intensity (ratio of peak intensity derived from benzene rings to the total integrated value), texture, and matrix resin impregnation were measured or calculated by the following methods, and processability was evaluated by the following methods. The whitening distance of the laminate obtained in this example was also measured by the following method. The results are shown in Table 1.
[0079] In Table 1, 3-methacryloxypropyltrimethoxysilane is referred to as "methacrylic", and the type of emulsion resin containing a copolymer resin of a styrene-based monomer and a (meth)acrylic acid ester-based monomer is referred to as "styrene / acrylic".
[0080] [Method of measuring adhesion amount] According to JIS R 3420, first, the mass of the crucible is measured and is defined as m0. Next, a surface-treated glass cloth test piece having a size of 30 cm in the longitudinal direction and 20 cm in the width direction is placed in the crucible and heated for 60 minutes in a dryer heated to 110 ° C. to dry the surface-treated glass cloth test piece. After drying, the crucible and the surface-treated glass cloth test piece are placed in a desiccator and cooled for 30 minutes. After cooling, the mass of the crucible and the surface-treated glass cloth test piece is measured and defined as m1. Next, the crucible and the surface-treated glass cloth test piece are placed in a muffle furnace heated to 625 ° C. and incinerated for 30 minutes. After incineration, the crucible and the surface-treated glass cloth test piece are placed in a desiccator again and cooled for 90 minutes. After cooling, the mass of the crucible and the surface-treated glass cloth test piece is measured and defined as m2. Next, the adhesion amount is calculated according to the following formula.
[0081] Adhesion amount (mass%)=(m1-m2)÷(m1-m0)×100 [Calculation method of glass transition temperature (Tg)] The Tg of a copolymer resin is calculated as a theoretical value from the following FOX equation using the Tg of a homopolymer measured by DSC.
[0082] 1 / Tg=W1 / Tg1+W2 / Tg2+···+W n / Tg n In the above formula, Tg represents the glass transition temperature (unit: K) of a polymer (copolymer) of n kinds of monomer components (monomers 1 to n). n represents the mass fraction of each monomer (1, 2, . . . , n) relative to the total amount of n monomer components, and Tg1, Tg2, . . . , Tg n represents the glass transition temperature (unit: K) of a homopolymer of each monomer (1, 2, . . . , n). The following values are used as the glass transition temperatures of the homopolymers of the monomers.
[0083] Styrene: 100℃, 2-Ethylhexyl acrylate: -70℃ Methyl methacrylate: 105℃ [ 1 Method for measuring the ratio of peaks originating from benzene rings to the total integral value in H-NMR measurement The surface-treated glass cloth cut to a size of 10 cm x 10 cm is immersed in 30 mL of toluene (special grade reagent, manufactured by Junsei Chemical Co., Ltd.) for 5 minutes and washed. The washing liquid is put into an evaporator to volatilize all the toluene. The remaining components are dissolved in chloroform-D1 (Sigma-Aldrich; 0.03 vol.% TMS, deuteration degree min. 99.8% for NMR spectroscopy (stabilized with silver)) containing tetramethylsilane (TMS) as an internal standard, and 1Measure with H-NMR (OXFORD INSTRUMENTS nuclear magnetic resonance analyzer (trade name: Pulsar HFC, 60 MHz). Perform at least 20 integrations, and taking the TMS peak as 0.0 ppm, divide the integral of the peaks whose peak tops are in the range of 6.3 to 7.2 ppm by the integral of all peaks excluding the TMS peak (peak at 0.0 ppm) and the peak of chloroform (CHCH3) contained in small amounts in chloroform-D1 (peak near 73.3 ppm); multiply this value by 100 to obtain the ratio of the peak of protons belonging to the benzene ring to the integral of the peaks of all protons.
[0084] [Method of measuring texture] The surface-treated glass cloth is cut to a size of 3 cm wide and 17 cm long to prepare a test piece. Next, the test piece is fixed at a portion 3 cm inside from one end of a flat stand of 5.5 cm x 3.5 cm horizontal to the ground at a height of 25 cm, and the remaining portion of 14 cm is hung outside the stand, and the height to which the surface-treated glass cloth hangs down vertically is measured. The larger the value, the softer the texture, and the smaller the value, the harder the texture.
[0085] [Method of measuring impregnation] The surface-treated glass cloth is cut out to 60 mm x 40 mm in size, centered on three points: a point 200 mm inside one end of the surface-treated glass cloth in the width direction, a point 200 mm inside the other end, and a point at the center of the width direction of the surface-treated glass cloth, to prepare impregnation evaluation test pieces. The impregnation evaluation test pieces are immersed in benzyl alcohol, and the time from immediately after immersion until the benzyl alcohol completely permeates the glass cloth pieces for impregnation evaluation is measured in the warp direction. Measurements are performed using five glass cloth pieces for impregnation evaluation at each measurement point, and the average value is calculated for each measurement point.
[0086] [Method of measuring whitening distance] The laminate was cut into a size of 7 cm x 4 cm using an NC router, and a 2 cm slit was made in each of the warp and weft directions to prepare a test piece. A 1 mol / L aqueous solution of NaOH (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was prepared and placed in a beaker, and heated to 60°C. The test piece was immersed in the aqueous NaOH solution for 30 hours, and the whitening distance due to peeling of the resin and glass interface in the warp and weft directions was measured at 24 points in each of the warp and weft directions at a magnification of 100 times using a digital microscope (manufactured by Keyence Corporation), and the average value was calculated to obtain the whitening distance. The whitening distance due to this peeling correlates with the insulation reliability of the printed wiring board, and the shorter the whitening distance, the higher the insulation reliability.
[0087] The values obtained by dividing the measured values of Examples 1 to 5 and Comparative Examples 1 to 7 by the measured value of Reference Example 1 described later, and the values obtained by dividing the measured value of Example 6 by the measured value of Reference Example 2 described later, were used as indexes for the Reference Examples. The indexes for the Reference Examples indicate improvement indexes of the whitening distance from the Reference Examples.
[0088] [Method of evaluating processability] In the manufacturing line from the heating and drying step after the formation of the second surface treatment layer on the surface-treated glass cloth to the winding up of the surface-treated glass cloth, the case where no wrinkles were generated was evaluated as "◯", the case where wrinkles were generated but did not leave marks was evaluated as "△", and the case where wrinkles that left marks were generated was evaluated as "X".
[0089] [Reference example 1] In this reference example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that the surface treatment of the glass cloth did not involve immersing the glass cloth in an emulsion resin treatment liquid.
[0090] Next, the surface-treated glass cloth obtained in this Reference Example was subjected to the same procedure as in Example 1 to measure the adhesion amount of the surface-treated layer, 1The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this reference example was measured in exactly the same manner as in Example 1. The results are shown in Table 1.
[0091] Example 2 In this example, a styrene-based emulsion resin, which is a copolymer of styrene and butadiene (product name: SBL 0597C, manufactured by ENEOS Corporation), was used as the styrene-based emulsion resin, and a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1. Since the styrene-based emulsion resin used in this example is a commercially available product, the content ratio of the styrene composition in the copolymer resin contained therein is unknown.
[0092] Next, the surface-treated glass cloth obtained in this example was subjected to the same procedure as in Example 1 to measure the adhesion amount of the surface-treated layer, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured to evaluate the processability. The glass transition temperature (Tg) of the emulsion resin is listed as a catalog value. In addition, the whitening distance of the laminate obtained in this example was measured exactly the same as in Example 1. The results are shown in Table 1.
[0093] In Table 1, the type of emulsion resin containing a copolymer resin of styrene and butadiene is described as "styrene / butadiene."
[0094] Example 3 In this example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that a styrene-based emulsion resin treatment liquid was used in which a styrene-based monomer (styrene) and a (meth)acrylic acid ester-based monomer (2-ethylhexyl acrylate and methyl methacrylate) were polymerized in a mass ratio of 70:30.
[0095] Next, the surface-treated glass cloth obtained in this example was subjected to the same procedures as in Example 1 to determine the adhesion amount of the surface treatment layer, the glass transition temperature (Tg) of the emulsion resin, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this example was measured in the same manner as in Example 1. The results are shown in Table 1.
[0096] Example 4 In this example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that a styrene-based emulsion resin treatment liquid was used in which a styrene-based monomer (styrene) and a (meth)acrylic acid ester-based monomer (2-ethylhexyl acrylate and methyl methacrylate) were polymerized in a mass ratio of 74:26.
[0097] Next, the surface-treated glass cloth obtained in this example was subjected to the same procedures as in Example 1 to determine the adhesion amount of the surface treatment layer, the glass transition temperature (Tg) of the emulsion resin, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this example was measured in the same manner as in Example 1. The results are shown in Table 1.
[0098] Example 5 In this example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that a styrene-based emulsion resin treatment liquid was used in which a styrene-based monomer (styrene) and a (meth)acrylic acid ester-based monomer (2-ethylhexyl acrylate and methyl methacrylate) were polymerized in a mass ratio of 81:19.
[0099] Next, the surface-treated glass cloth obtained in this example was subjected to the same procedures as in Example 1 to determine the adhesion amount of the surface treatment layer, the glass transition temperature (Tg) of the emulsion resin, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this example was measured in the same manner as in Example 1. The results are shown in Table 1.
[0100] Example 6 In this example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride was used as the silane coupling agent.
[0101] Next, the surface-treated glass cloth obtained in this example was subjected to the same procedures as in Example 1 to determine the adhesion amount of the surface treatment layer, the glass transition temperature (Tg) of the emulsion resin, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this example was measured in exactly the same manner as in Example 1. In this example, the whitening distance was calculated by dividing the measured value of this example by the measured value of Reference Example 2 described later, and the result was used as an index for the Reference Example. The results are shown in Table 1.
[0102] In Table 1, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride is referred to as "cationic."
[0103] [Reference example 2] In this reference example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 6, except that the surface treatment of the glass cloth did not involve immersing the glass cloth in an emulsion resin treatment liquid.
[0104] Next, the surface-treated glass cloth obtained in this Reference Example was subjected to the same procedure as in Example 1 to measure the adhesion amount of the surface-treated layer, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this reference example was measured in exactly the same manner as in Example 1. The results are shown in Table 1.
[0105] Comparative Example 1 In this comparative example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that an emulsion resin treatment liquid containing a copolymer resin of acrylic resin (2-ethylhexyl acrylate and methyl methacrylate) was used. The emulsion resin does not contain any structural units derived from styrene-based monomers.
[0106] Next, the surface-treated glass cloth obtained in this comparative example was subjected to the same procedures as in Example 1 to determine the adhesion amount of the surface treatment layer, the glass transition temperature (Tg) of the emulsion resin, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this comparative example was measured in exactly the same manner as in Example 1. The results are shown in Table 2.
[0107] In Table 2, 3-methacryloxypropyltrimethoxysilane is referred to as "methacrylic", and the type of emulsion resin containing the polymer resin of the (meth)acrylic acid ester monomer is referred to as "acrylic".
[0108] Comparative Example 2 In this comparative example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that a styrene-based emulsion resin treatment liquid was used in which a styrene-based monomer (styrene) and a (meth)acrylic acid ester-based monomer (2-ethylhexyl acrylate and methyl methacrylate) were polymerized in a mass ratio of 40:60.
[0109] Next, the surface-treated glass cloth obtained in this comparative example was subjected to the same procedures as in Example 1 to determine the adhesion amount of the surface treatment layer, the glass transition temperature (Tg) of the emulsion resin, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this comparative example was measured in exactly the same manner as in Example 1. The results are shown in Table 2.
[0110] In Table 2, the type of emulsion resin containing a copolymer resin of a styrene monomer and a (meth)acrylic acid ester monomer is described as "styrene / acrylic".
[0111] Comparative Example 3 In this comparative example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that a styrene-based emulsion resin treatment liquid was used in which a styrene-based monomer (styrene) and a (meth)acrylic acid ester-based monomer (2-ethylhexyl acrylate and methyl methacrylate) were polymerized in a mass ratio of 54:46.
[0112] Next, the surface-treated glass cloth obtained in this comparative example was subjected to the same procedures as in Example 1 to measure the adhesion amount of the surface treatment layer, the glass transition temperature (Tg) of the styrene-based emulsion resin, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this comparative example was measured in exactly the same manner as in Example 1. The results are shown in Table 2.
[0113] Comparative Example 4 In this comparative example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that a styrene-based emulsion resin treatment liquid was used in which a styrene-based monomer (styrene) and a (meth)acrylic acid ester-based monomer (2-ethylhexyl acrylate and methyl methacrylate) were polymerized in a mass ratio of 93:7.
[0114] Next, the surface-treated glass cloth obtained in this comparative example was subjected to the same procedures as in Example 1 to measure the adhesion amount of the surface treatment layer, the glass transition temperature (Tg) of the styrene-based emulsion resin, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this comparative example was measured in exactly the same manner as in Example 1. The results are shown in Table 2.
[0115] Comparative Example 5 In this comparative example, a surface-treated glass cloth and a laminate were obtained in exactly the same manner as in Example 1, except that a styrene-based emulsion resin treatment liquid was used in which a styrene-based monomer (styrene) and a (meth)acrylic acid ester-based monomer (2-ethylhexyl acrylate and methyl methacrylate) were polymerized in a mass ratio of 88:12.
[0116] Next, the surface-treated glass cloth obtained in this comparative example was subjected to the same procedures as in Example 1 to measure the adhesion amount of the surface treatment layer, the glass transition temperature (Tg) of the styrene-based emulsion resin, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this comparative example was measured in exactly the same manner as in Example 1. The results are shown in Table 2.
[0117] Comparative Example 6 In this comparative example, the solid content of the silane coupling agent in the silane coupling agent treatment liquid was 10.0 mass %, and the glass cloth was not immersed in an emulsion resin treatment liquid at all in the surface treatment of the glass cloth, but other than that, the surface-treated glass cloth and laminate were obtained in exactly the same manner as in Example 1. In this comparative example, the solid content of the silane coupling agent in the silane coupling agent treatment liquid was 10.0 mass %, and as a result, the adhesion amount of the surface treatment layer was increased compared to Example 1.
[0118] Next, the surface-treated glass cloth obtained in this comparative example was subjected to the same procedure as in Example 1 to measure the adhesion amount of the surface-treated layer, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this comparative example was measured in exactly the same manner as in Example 1. The results are shown in Table 2.
[0119] Comparative Example 7 In this comparative example, the solid content of the silane coupling agent in the silane coupling agent treatment liquid was 20.0 mass %, and the glass cloth was not immersed in an emulsion resin treatment liquid at all in the surface treatment of the glass cloth, but other than that, the surface-treated glass cloth and laminate were obtained in exactly the same manner as in Example 1. In this comparative example, the solid content of the silane coupling agent in the silane coupling agent treatment liquid was 20.0 mass %, and as a result, the adhesion amount of the surface treatment layer was increased compared to Example 1.
[0120] Next, the surface-treated glass cloth obtained in this comparative example was subjected to the same procedure as in Example 1 to measure the adhesion amount of the surface-treated layer, 1 The ratio of the integral value of the peak of the protons belonging to the benzene ring to the integral value of the peak of all protons measured by H-NMR, the texture, and the impregnation of the matrix resin were measured or calculated to evaluate the processability. In addition, the whitening distance of the laminate obtained in this comparative example was measured in exactly the same manner as in Example 1. The results are shown in Table 2.
[0121] [Table 1]
[0122] [Table 2]
[0123] From Table 1, it can be seen that the surface treatment layer contains a silane coupling agent and a structural unit derived from a styrene-based monomer, 1 The surface-treated glass cloths of Examples 1 to 6, which contain a surface treatment resin in which the integral value of the proton peaks belonging to a benzene ring, as measured by H-NMR, is in the range of 28 to 46% of the integral value of the peaks of all protons, can obtain excellent adhesion to the matrix resin, and even if the adhesion amount of the surface treatment layer is increased to 0.8 mass % or more, the impregnation of the matrix resin into the glass fiber is not impaired, the texture does not become excessively hard, and it is clear that excellent processability can be obtained when producing a prepreg.
[0124] On the other hand, from Table 2, it can be seen that the surface treatment layer does not contain any structural units derived from styrene-based monomers, 1 A surface-treated glass cloth of Comparative Example 1 containing a surface treatment resin having an integral value of 0 for the peak of protons belonging to a benzene ring as measured by H-NMR; and 1 The surface-treated glass cloths of Comparative Examples 2 and 3, in which the integral value of the proton peaks belonging to the benzene ring measured by H-NMR does not reach 28% of the integral value of the peaks of all protons, have a hard feel and are unable to obtain excellent processability. Not only does the impregnation of the glass fibers of the surface-treated glass cloth with the matrix resin decrease, but the adhesion of the matrix resin to the surface-treated glass cloth is also clearly inferior to the surface-treated glass cloths of Examples 1 to 6.
[0125] Also, from Table 2, 1According to the surface-treated glass cloths of Comparative Examples 4 and 5, in which the integral value of the proton peaks belonging to the benzene ring measured by H-NMR exceeds 46% of the integral value of the total proton peaks, it is clear that the impregnation of the glass fibers of the surface-treated glass cloth with the matrix resin is reduced and the adhesion of the matrix resin to the surface-treated glass cloth is also inferior to the surface-treated glass cloths of Examples 1 to 6.
[0126] Furthermore, from Table 2, it is clear that in the surface-treated glass cloths of Comparative Examples 6 and 7, in which the solid content of the silane coupling agent in the silane coupling agent treatment liquid was increased while no treatment of immersing the glass cloth in an emulsion resin treatment liquid was performed, the impregnation of the matrix resin into the glass fibers of the surface-treated glass cloth was reduced, and the adhesion of the matrix resin to the surface-treated glass cloth was also significantly inferior to the surface-treated glass cloths of Examples 1 to 6.
Claims
1. A surface-treated glass cloth having a surface treatment layer on a surface thereof, the surface treatment layer contains a silane coupling agent and a structural unit derived from a styrene-based monomer, 1 and a resin for surface treatment, in which the integral value of the peak of a proton assigned to a benzene ring, as measured by H-NMR, is in the range of 28 to 46% of the integral value of the peaks of all protons.
2. 2. The surface-treated glass cloth according to claim 1, wherein the silane coupling agent is methacrylsilane.
3. 2. The surface-treated glass cloth according to claim 1, wherein the styrene-based monomer is one or more monomers selected from styrene-based monomers represented by the following general formula (1): 【Chemistry 1】 [In the formula, R 1 is hydrogen or an alkyl group having 1 to 2 carbon atoms; R 2 ~R 6 each independently represents a hydrogen atom, a halogen atom, an alkyl group, an alkenyl group, an alkynyl group, or an aryl group, and may contain a heteroatom.
4. 2. The surface-treated glass cloth according to claim 1, wherein the surface treatment layer comprises a first surface treatment layer containing a silane coupling agent and a second surface treatment layer containing the surface treatment resin.
5. 2. The surface-treated glass cloth according to claim 1, wherein the amount of the surface treatment layer attached is in the range of 0.8 to 5.0 mass % based on the total amount of the surface-treated glass cloth.
6. 2. The surface-treated glass cloth according to claim 1, wherein a dielectric loss tangent at a measurement frequency of 10 GHz is in the range of 0.0001 to 0.0040.
7. A prepreg comprising the surface-treated glass cloth according to any one of claims 1 to 6.
8. A printed wiring board comprising the surface-treated glass cloth according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation of copperrclad laminate
JP1979074884A
Sizing agent for glass fiber
JP1985221344A
Thermosetting resin prepreg
JP1989221434A
Glass fiber reinforced prepreg, laminate, electronic circuit board, and fabric assembly method
JP2002527538A
Fiber material, prepreg, metal-clad laminate, and circuit board
JP2018115225A